Symbols in hindu political communication by the governor of bali regarding pusat kebudayaan bali (symbolic convergence analysis) - Ida Bagus Ngurah Tri Pramana (Bali Tourism Board, 2023)
In the news on Tempo.co Online Media on April 28, 2022, at 09.43 WIB with the title Towards a New Era of Bali, Built Cultural Center Areas, Governor of Bali for the 2018 – 2023 period, I Wayan Koster made several statements relating to Hindu political communication. In several accounts, the Governor of Bali, I Wayan Koster, used several symbols considered historical representations during the Hindu Gelgel Kingdom that are repeated in the present. In this study, researchers used a qualitative descriptive research method with an analysis of Symbolic Concentration Theory to analyze fantasy themes conveyed as symbols in political communications contained in the news. Based on the study, it can be stated that a fantasy theme correlates with the political communication goals of the Governor of Bali as a political communicator, namely Character, Plot, Place and Supporting Intermediaries. In this news, the Governor of Bali, I Wayan Koster, delivered rhetoric by using several symbols such as Raja Dalem Waturenggong (Character), the 500-year journey of the evolution of civilization in Bali since the time of the Gelgel Kingdom (Groove), Ex-Excavation Area C Gunaksa, Klungkung (Place), Concept Bali Padma Bhuwana, Bali Cultural Center Area, Monumental and historical masterpiece, new Economic Center, as well as a symbol of pride and happiness for Balinese people, and New Era of Balinese Civilization (Supporting Intermediaries). The use of this symbol aims to strengthen the political position of the Provincial Government of Bali, in this case, the leadership of the Governor of Bali, I Wayan Koster, through the achievements that have been achieved through the Development of the Bali Cultural Center which is located in Ex Excavation C, Gunaksa. Apart from that, the Governor of Bali's statement also aims to influence the Balinese people to unite in supporting government programs to realize harmonious social conditions following the Padma Bhuwana concept.